No beast so fierce : the terrifying true story of the Champawat Tiger, the deadliest animal in history - Huckelbridge, Dane (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"American Sniper meets Jaws: The gripping true account of the Champawat Tiger, the deadliest animal of all time (killer of an astonishing 436 humans), and Jim Corbett, the legendary hunter who brought it down in 1907"--